ARMEN MUKHTAR DAN PERANNYA DIDALAM PEMEKARAN KABUPATEN SOLOK-SELATAN (1999-2004) - -, HARYANTONI - (Pendidikan Sejarah, 2014)
is. (1) How is Armen Mukhtarâs childhood in getting education and in his family. (2) How are his efforts or the ways which have been done by Armen Mukhtar in Developing regency south Solok. This research uses historic method through biography approach or study which is suitable with the rule of historic research that is done doing some steps. They are (1) Heurisctic is collecting the data from the written and spoken sources. (2) Sources criticize through external and internal criticize. (3) Interpretation is classifying and reconstructing into story form. (4) Historiography is the explanation the result of the research in thesis from. The results of the research which are gotten from the field state that: Armen Mukhtar is a volunteer from Muara Labuh regency south Solok. Armen Mukhtar has amazing ideas in arranging the ways and has good knowledge in education. Armen Mukhtar is also known as a promoter for all activities which are done to guide the other volunteers. Armen Mukhtar is also a source of all information which relates to The Development of regency south Solok. He has given all efforts and thoughts for doing the development of regency south Solok. By doing all of the efforts, Armen Mukhtar can be said as a volunteer for the region and he is suitable to be given a reward for all of his service for the region.